Blending to Treat Expulsion in a Child with Food Refusal. (26th May 2015) - Sharp, William G.; Trumbull, Ashley; Lesack, Roseanne
<x xml:space="preserve">Abstract</x> The current study examined the effect of blending established foods and non‐preferred foods to treat expulsions in a three‐year‐old girl with food refusal and gastrostomy‐tube dependence. Treatment involving differential reinforcement of acceptance, non‐removal of the spoon, and re‐presentation increased consumption of 12 out of the 16 pureed foods; however, high levels of expulsion of four foods continued to disrupt meals. Results showed reduced rates of expulsion and increased mouth clean during blending, evaluated empirically using an ABAB design. Copyright © 2015 John Wiley & Sons, Ltd.